ISLAMIC RELIGIOUS EDUCATION CURRICULUM PLANNING IN FACING THE ERA OF DISRUPTION IN ISLAMIC RELIGIOUS HIGHER EDUCATION - Karim, Hamdi Abdul; Pahrudin, Agus; Masykur, Rubhan; Hadi, Mukhtar; Adzkiyaunuha, Moh (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
Background: The background of this study relates to the challenges faced by Islamic higher education institutions in the midst of the disruption era, where rapid changes in technology and social dynamics necessitate innovation in educational curricula. The disruption era has influenced various aspects of life, including learning methods and the delivery of knowledge. Therefore, it is essential to evaluate and redesign the educational curriculum to address these challenges and remain relevant to societal needs. Purpose: This research aims to analyze curriculum planning in Islamic higher education institutions, specifically in Metro City, in response to these changes. Method: Using qualitative research methods and a phenomenological approach, this study collects data through interviews, observations, and documentation. The data analysis process is conducted through three activity flows: data reduction, data presentation, and drawing conclusions. Result: The results of the study on the Islamic religious education curriculum planning at Islamic colleges in Metro City found several procedures that serve as references in curriculum planning, namely: foundations in curriculum planning, parties involved in curriculum planning, principles in curriculum planning, characteristics in curriculum planning, and components in curriculum planning. Conclusion: The conclusion of this research emphasizes the importance of curriculum planning that is responsive to social and technological changes in Islamic higher education. Involvement from various stakeholders and relevant design will produce quality graduates who are prepared to face global challenges in the disruption era.